2014
DOI: 10.1002/uog.13357
|View full text |Cite
|
Sign up to set email alerts
|

‘Post-LA space index’ as a potential novel marker for the prenatal diagnosis of isolated total anomalous pulmonary venous connection

Abstract: Objectives To review the fetal echocardiograms of patients with total anomalous pulmonary venous connection (TAPVC) in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 16 publications
6
73
1
Order By: Relevance
“…In normal fetuses, the space posterior to the left atrium (LA) is usually narrow, with the descending aorta and being close to each other . We previously reported that this space is wider in fetuses with total anomalous pulmonary venous connection (TAPVC), a rare form of severe congenital heart disease that requires emergency neonatal surgery associated with a high mortality . It is still difficult to detect TAPVC prenatally because the four‐chamber view looks normal .…”
Section: Introductionmentioning
confidence: 99%
“…In normal fetuses, the space posterior to the left atrium (LA) is usually narrow, with the descending aorta and being close to each other . We previously reported that this space is wider in fetuses with total anomalous pulmonary venous connection (TAPVC), a rare form of severe congenital heart disease that requires emergency neonatal surgery associated with a high mortality . It is still difficult to detect TAPVC prenatally because the four‐chamber view looks normal .…”
Section: Introductionmentioning
confidence: 99%
“…Forest plot of rate of favorable outcome (alive operated) for fetuses with total anomalous pulmonary venous connection, reported in 10 primary studies and five case reports. Only first author of each study is given.…”
Section: Resultsmentioning
confidence: 99%
“…Forest plots for studies on cases of total anomalous pulmonary venous connection, of rate of prenatally detected ventricular disproportion reported in eight primary studies and five case reports (a), increased area behind left atrium reported in 10 primary studies and four case reports (b) and vertical vein reported in 10 primary studies and three case reports (c). Only first author of each study is given.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. et al described a novel and efficient ultrasound marker of TAPVC, the "post-LA space index". It has been proved, that if the ratio of the descending aortaleft atrium distance to the diameter of descending aorta is higher than 1.27, the diagnosis of TAPVC is confirmed with a sensitivity of 100% and specificity of 99% 16 . Doppler echocardiography may also be useful in diagnosis of TAPVC.…”
Section: Discussionmentioning
confidence: 99%